Simulation-based Approaches for Warehouse Layout Optimization in Logistics - Tulli, Sai krishna Chaitanya (International Journal of Scientific Research and Management (IJSRM), 2020)
Warehouse layout optimization is a critical component in enhancing operational efficiency, minimizing costs, and improving overall logistics performance. This research explores the role of simulation-based approaches in optimizing warehouse layouts, focusing on their ability to model complex scenarios and predict outcomes with precision. The study reviews existing literature on traditional and modern optimization techniques, identifies key gaps, and proposes a robust simulation framework. Using advanced tools like discrete event simulation and agent-based modeling, the study demonstrates significant improvements in storage utilization, picking efficiency, and throughput. Key metrics are analyzed to evaluate the impact of optimized layouts on logistics operations. The findings highlight the advantages of simulation-based methods, including flexibility, cost-effectiveness, and scalability, while also addressing their limitations. This research provides practical recommendations for integrating simulation tools into warehouse design processes, offering a roadmap for logistics managers and decision-makers. Future research directions emphasize the integration of simulation with emerging technologies such as artificial intelligence and IoT for dynamic and adaptive warehouse layouts.